Pengaruh Kombinasi Pemberian Massage Effleurage dengan Nigella Sativa Oil Terhadap Penurunan Risiko Terjadinya Ulkus Dekubitus - Siti Karomah; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Journal of Health, Medical, and Psychological Studies, 2025)
Pressure ulcers are conditions characterized by damage to the anatomical structure and normal function of the skin caused by continuous external pressure on prominent bony areas. This study was conducted to determine the effect of a combination of effleurage massage and Nigella sativa oil on reducing the risk of pressure ulcer development. Pressure ulcers are a common nursing problem, particularly among individuals with limited mobility and those undergoing prolonged bed rest. This study employed a quantitative approach using a quasi-experimental one-group design with post-intervention measurement. The sample consisted of 18 respondents who met the inclusion criteria and were determined using the Federer formula. All respondents received an intervention in the form of a combination of effleurage massage and Nigella sativa oil in accordance with established procedures. The risk of pressure ulcer development was assessed after the intervention using a standardized risk assessment instrument. The data were analyzed using appropriate statistical tests. The results showed a statistically significant reduction in the risk of pressure ulcer development after the intervention, with a p-value of 0.003. This study concludes that the combination of effleurage massage and Nigella sativa oil has a significant effect on reducing the risk of pressure ulcers.